2007
DOI: 10.1142/s0217979207037247
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Holographic Imaging Using Photorefractive Polymers Based on a Boronate-Derivative Nonlinear Chromophore

Abstract: We report dynamic holographic imaging with organic photorefractive polymer composites, doped with the electro-optic chromophore (2-(p-chlorophenyl)-(3′-nitrobenzo[d])-(4′′-methoxybenzo[h])-1,3-dioxa-6-aza-2-boracyclonon-6-ene, a push-pull molecule derived from a new class of boronates. The composites are based on the photoconductor poly(9-vinylcarbazole) (PVK) as the polymer matrix, and 9-ethylcarbazole (ECZ) as the plasticizer, with the fullerene C 60 as sensitizer. A tilted four-wave mixing geometry was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Block copolymers featuring a relatively long PEO segment formed stable micellar solutions in water with luminescence characteristics similar to those of the respective (water-insoluble) homopolymers, suggesting potential applications as nanosized fluorophores in biological environments. Among other interesting O-B-N-containing organoboron compounds are the so-called "push-pull" type of molecules [106][107][108]. These compounds derive from the well-known stilbene backbone, to which an arylboron (ArB) fragment has been added.…”
Section: O-b-n Boronatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Block copolymers featuring a relatively long PEO segment formed stable micellar solutions in water with luminescence characteristics similar to those of the respective (water-insoluble) homopolymers, suggesting potential applications as nanosized fluorophores in biological environments. Among other interesting O-B-N-containing organoboron compounds are the so-called "push-pull" type of molecules [106][107][108]. These compounds derive from the well-known stilbene backbone, to which an arylboron (ArB) fragment has been added.…”
Section: O-b-n Boronatesmentioning
confidence: 99%
“…Electric-field-induced second-harmonic measurements of the nonlinear optical response revealed that the nature of the phenyl-boron moieties has a modest influence on the molecular hyperpolarizabilities. Among other interesting O-B-N-containing organoboron compounds are the so-called "push-pull" type of molecules [106][107][108]. These compounds derive from the well-known stilbene backbone, to which an arylboron (ArB) fragment has been added.…”
Section: O-b-n Boronatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 1a belongs to the orthorhombic space group Icab, 2b to the triclinic space group P 1 and 3b to the monoclinic C2/c. Boron 13 C NMR (ppm) and IR (cm À1 ) data for compounds 1-3, 1a-1c, 2a-2c and 3a-3d compounds 1a and 3b contain one crystallographically independent molecule while 2b has two independent molecules that show the same structure in the asymmetric unit. The bond distance observed in the dative N ?…”
Section: Molecular Structurementioning
confidence: 99%
“…The results suggest that modulation could be achieved by rotation of the phenyl around the boron-carbon bond. One of these boron chromophores has been used for NLO dynamic holographic imaging in photorefractive polymers [13].…”
Section: Introductionmentioning
confidence: 99%